1-MCP treatment enhanced expression of genes controlling endosperm cell division and starch biosynthesis for improvement of grain filling in a dense-panicle rice cultivar. (May 2016) - Panda, B.B.; Badoghar, A.K.; Sekhar, S.; Shaw, B.P.; Mohapatra, P.K.
Highlights: Grain filling is poor in the inferior spikelets located on basal part of panicle in the new dense panicle rice cultivars. Inferior spikelets did not fill properly because they produced more ethylene at anthesis compared to superior spikelets. High ethylene production resulted in greater expression of ethylene receptor and signal transducer genes and low cell number. Repressed ethylene action by 1-MCP enhanced expression of starch synthesizing enzyme genes for better grain filling. 1-MCP treatment increased expression of endosperm cell cycle regulator genes more in inferior spikelets to improve seed size. Abstract: High ethylene production in dense-panicle rice cultivars impacts grain filling. 1-MCP (ethylene action inhibitor) treatment increased assimilates partitioning, cell number and size and expression of starch synthesizing enzyme genes of developing caryopses mostly in the basal spikelets of panicle at early post-anthesis stage. The gain in cell number was less compared to the increase of size. High ethylene production in spikelets matched with greater expression of ethylene receptor and signal transducer genes. Genes encoding cell cycle regulators CDK, CYC and CKI expressed poorly on 9 DAA. 1-MCP treatment enhanced their expression; the increase of expression was higher for CDKs and lower for CKIs in basal compared to apical spikelets. Greater expression of CDKB2:1 might have lifted cytokinesis of nascent peripheral cells of endosperm, while promotion of CDKAs, CYCD2:2 and inhibition of CYCB2:2 expression contributed to endoreduplication of central cells increasing cell size and DNA ploidy level. It is concluded that the process of endoreduplication, which begins at mid-grain filling stage, is crucially linked with the final caryopsis size of rice grain. The enhanced endosperm growth brought about by repressed ethylene action during the first few days after anthesis seems to be associated with the overall increased cell cycle activity and sink strength.